Electrochemical actuation behaviors and mechanisms of bulk nanoporous Ni-Pd alloy. (August 2017) - Zhang, Jie; Lv, Lanfen; Gao, Hui; Bai, Qingguo; Zhang, Chi; Zhang, Zhonghua
Abstract: Metallic actuators have recently aroused great interests, and alloying of noble element with earth-abundant metal is essential to lower the cost of actuation materials while keeping a significant strain response. Here, we report the design/fabrication of bulk nanoporous nickel-palladium alloy by dealloying. The alloy with a hierarchically porous structure shows different actuation behaviors in different electrolytes, which are correlated with the adsorption/desorption of hydrogen/hydroxyl and the nature (clean or oxide-cover) of ligament surface. The maximum reversible strain of the nickel-palladium actuator could reach 0.47% in potassium hydroxide solution, which is more competitive compared with other metallic actuation materials. Graphical abstract: The np-Ni80 Pd20 with a hierarchically porous structure could trigger reversible strain of 0.47% in 1.0 M KOH solution.